Judicial Analysis of Collective and Continuing Theft Based on Indonesian Criminal Law - Michael Victor Manalu; I Ketut Seregig (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study examines judicial considerations in cases of theft committed jointly (medeplegen) as a continued act (voortgezette handeling) based on Indonesian criminal law, focusing on Decision No. 104/Pid.B/2025/PN.Tjk. Research Methodology: This research uses a normative-empirical juridical approach, combining statutory analysis with field research including interviews with judges, prosecutors, and investigators related on the problem in this research. Results: The court correctly applied Article 363 paragraph (1) sub-4 in conjunction with Article 64 paragraph (1) of the Kitab Undang-Undang Hukum Pidana (KUHP). The elements of joint participation and continuing acts were established through evidence of functional cooperation and unity of intent (één wilsbesluit). Although physical evidence was unavailable at trial, the conviction was lawfully established through consistent witness testimonies and the defendant’s confession in accordance with the negative statutory proof system (negatief wettelijk). Conclusions: The decision reflects proper legal reasoning by balancing juridical, philosophical, and sociological considerations. The sentence imposed fulfills the objectives of legal certainty, justice, and utility. Limitations: This study focuses on a single district court decision, limiting broader generalization in Indonesian jurisprudence. Contributions: This study contributes to the doctrinal understanding of collective criminal liability and continuing offenses in Indonesian criminal law, particularly regarding evidentiary construction in the absence of physical evidence.